The TRAINING NEEDS ANALYSIS FOR INDUSTRY USING THE IRWIN GOLDSTEIN METHOD APPROACH - Kusmiati, Mia; Sundari, Sri (Universitas Indonesia Membangun (Inaba), 2022)
A good organization is supported by good management and employees who have adequate knowledge and skills in carrying out their functions and duties. The organization provides a management system that makes it easy for members of the organization to run the system so that organizational performance is easy to control. Employees with adequate quality and competence are able to bring the organization to a more advanced direction. They are trained and have the desire to continue to grow and develop into individuals needed by the organization in achieving its goals. The rapid development of technology and industry today has resulted in many adjustments and system changes in management. In the new normal era where all work activities have begun to be directed online-based, many organizations carry out training needs analysis in obtaining information on what training is suitable to be held in improving organizational performance. This study describes the theory of training needs analysis for organizations. And this study aims to obtain information about what is needed in analyzing training needs for organizations. The research method used is a qualitative method using a literature review approach. The results of this study were selected as a training needs analysis tool by using an organizational analysis approach to the strategy of the Irwin Goldstein method which sets 4 indicators, namely: (1) organizational goals; (2) organizational resources; (3) organizational climate; and (4) environmental constraints.